2019
DOI: 10.1177/1077558719832797
|View full text |Cite
|
Sign up to set email alerts
|

When the Evidence Basis Breeds Controversies: Exploring the Value Profile of Robotic Surgery Beyond the Early Introduction Phase

Abstract: This article investigates qualitatively the value profile of the da Vinci® surgical robot after almost two decades of extensive clinical use and research. We aimed to understand whether the swiftly growing body of published studies on robotic prostate surgery can now, that is, beyond an early stage, guide decisions on the acquisition, procurement, and public provision of this innovation. We explored both published studies and the perspectives of diverse stakeholders in the Netherlands. Both arenas represent co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Nowadays RAS is introduced into a variety of surgical specialities with immense evidence generated solely on Intuitive-Surgical products of 13,500 peer-reviewed articles, averaging one publication every 4 h [ 51 ]. Despite this huge evidence base and the broad application, it is still unknown if RAS overcomes the limitations of conventional approaches [ 51 53 ]. Therefore, we aimed to systematically analyse the effectiveness and safety of RAS in 14 thoracic and visceral indications compared to laparoscopic or open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays RAS is introduced into a variety of surgical specialities with immense evidence generated solely on Intuitive-Surgical products of 13,500 peer-reviewed articles, averaging one publication every 4 h [ 51 ]. Despite this huge evidence base and the broad application, it is still unknown if RAS overcomes the limitations of conventional approaches [ 51 53 ]. Therefore, we aimed to systematically analyse the effectiveness and safety of RAS in 14 thoracic and visceral indications compared to laparoscopic or open surgery.…”
Section: Discussionmentioning
confidence: 99%
“…With implementation of modern minimally invasive surgical technology, this strategy seems practical because several trials have shown a rapid recovery after minimally invasive surgery. [1][2][3][4][5] Not only is outpatient care after robotic prostatectomy an interest for health care systems, a high rate of patient/family satisfaction (87.5%-100%) has also been reported with this care pathway. 7,16 The International Association for Ambulatory Surgery defines ambulatory surgery (-extended recovery) as overall length of postoperative hospital stay £23 hours.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive surgery has been considered as one of the novel ways for improving the efficiency of health care by offering a shorter hospital stay and a smooth convalescence despite adoption of often ex-pensive and innovative technologies. 1,2 This notion has been shown in robotic radical prostatectomy (RRP) literature, as a widespread standard of care for minimally invasive surgical management of localized prostate cancer. With comparable oncologic and functional outcomes, significant advantages in terms of postoperative recovery parameters have been shown in randomized trials.…”
Section: Introductionmentioning
confidence: 99%
“…In order to increase the transferability of our findings, we attempted to select a diverse set of surgical devices, and a diverse set of participants that worked on different devices 21. These could range from robotic systems such as the Da Vinci System22 to simpler devices like novel surgical sutures 23. These innovations can vary in technical complexity, their impact on the surgical workflow,24 clinical outcomes,25 26 safety issues26 27 and impact on patients’ lives 26.…”
Section: Methodsmentioning
confidence: 99%